2011
DOI: 10.1039/c1mb05196b
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolic footprinting reveals a surprising breadth of metabolite uptake and release by Synechococcus sp. PCC 7002

Abstract: Cyanobacteria are important primary producers in diverse ecosystems, yet little is known about the extent of their metabolic interactions with the environment. We have used an integrated, untargeted metabolic footprinting approach to systematically evaluate the uptake and release of metabolites between a model marine cyanobacterium Synechococcus sp. PCC 7002 and different growth media. It was found that 47 out of 202 detected metabolites were consumed, and an additional 55 metabolites were released by the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 36 publications
1
63
0
Order By: Relevance
“…The compound may be enzymatically transformed to a different compound outside of the cell and then utilized, or it may be simply be imported into the cell and not participate in any metabolism. While strange, the latter scenario has been reported to occur in Cyanobacteria [16].
Fig.
…”
Section: Resultsmentioning
confidence: 85%
“…The compound may be enzymatically transformed to a different compound outside of the cell and then utilized, or it may be simply be imported into the cell and not participate in any metabolism. While strange, the latter scenario has been reported to occur in Cyanobacteria [16].
Fig.
…”
Section: Resultsmentioning
confidence: 85%
“…However, uptake of amino acids by Synechococcus spp. has been documented previously in culture (Baran et al, 2011) and during in situ incubation experiments (Zubkov et al, 2003;Michelou et al, 2007). Taken together, this information emphasizes the need for quantifying the autotrophic contribution to DOM turnover in order to improve models of the ocean carbon cycle.…”
Section: Synechococcus Elongatusmentioning
confidence: 82%
“…Further, the composition of phytoplankton exudates influences microbial community structure over spatial and temporal gradients (Cottrell and Kirchman, 2000;Nelson and Carlson, 2012;Landa et al, 2013). Investigations of DOM released by phytoplankton have shown that its composition is quite variable and is influenced by phylogeny (Romera-Castillo et al, 2011;Becker et al, 2014) and growth conditions (Grossart and Simon, 2007;Baran et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As mass spectrometry (MS) instruments such as Fourier Transform Ion Cyclotron Resonance (FTICR/MS) (Hirai et al, 2004), capillary electrophoresis (CE/MS) (Soga et al, 2003;Edwards et al, 2006), and liquid chromatography (LC/MS) (Baran et al, 2011(Baran et al, , 2013 are commonly used, they are not widely available. In contrast, GC/MS is a widely-used and generally moreaccessible instrument to microbiologists and soil scientists due its low operational cost, availability of curated metabolite spectral databases, broad analytical scope with good coverage of metabolite classes (carbohydrates, alcohols, sterols, amino acids, fatty acids, etc), as well as widespread application to phospholipid fatty acid analysis (Buyer and Sasser, 2012).…”
Section: The Use Of Untargeted Metabolomics To Understand Dom Composimentioning
confidence: 99%